Development of Quality Standards of Aegle marmelos L. Leaves - S. Ahmad, B. Ali, Junaid Aslam, N.A. Siddique, M. Mujeeb, S.H. Ansari, (Journal of Phytology, 2010)
Aegle marmelos L (Rutaceae) is a moderately size deciduous tree, growing wild throughout the deciduous forest of India. It is commonly used in day to day life. In present investigation an attempt has been made for the pharmacognostical standardization and evaluation of Aegle marmelos leaves. The pharmacognostical evaluation comprises of detailed macroscopy, powdered microscopy, fluorescence analysis, quantitative microscopy and physical constants such as ash and extractive values. The leaves extracts were subjected to preliminary phytochemical screening. The data obtained in present study will serve as valuable tool for identification, authentication and detection of adulterants, standardization and quality control of the drug. The developed technique will also be useful for the standardization of formulations containing A. marmelos.Ã‚Â